Detection of Wild-type Yellow Fever Virus in Breast Milk. Issue 1 (January 2020) - Ribeiro, Ana Freitas; Brasil, Lucas Mendes Cunha de Resende; Prada, Renato Martins; Nogueira, Juliana Silva; Maeda, Adriana Yurika; Sztajnbok, Jaques
Abstract : Yellow fever is an endemic disease in tropical areas in America and Africa. We report a case where the wild-type yellow fever virus was detected in a breast milk sample of a 33-year-old woman, from a rural area in the municipality of São Paulo, thus highlighting a potential risk for transmission of yellow fever virus through breast-feeding.